2022
DOI: 10.1093/ndt/gfac045
|View full text |Cite
|
Sign up to set email alerts
|

Urea levels and cardiovascular disease in patients with chronic kidney disease

Abstract: Background Elevated serum urea levels are common in moderate-to-advanced CKD. Several studies have shown that urea is a direct and indirect uremic toxin, especially with regard to cardiovascular disease. We sought to determine whether serum urea levels are associated with adverse cardiovascular events and death before renal replacement therapy (RRT) in patients with CKD. Methods CKD-REIN is a prospective cohort of CKD nephrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Besides, regarding safety issues, previous studies have proven that, if the daily calorie intake is sufficient, sVLPDs or sLPDs in CKD patients could be safe, and even had some metabolic benefits, namely less hyperphosphatemia, less hyperparathyroidism, lower blood pressure, and gut microbiota modulation, which may additionally contribute to long-term cardiovascular protective effect and patient survival. One previous cohort study demonstrated that serum urea level is associated with CV outcomes in CKD patients, and further suggested a reduction of urea by nutritional therapy may thus be beneficial in reducing CV risks [ 33 ]. Actually, in this study, if we combined all common adverse events in CKD patients, including ESKD requiring dialysis, MACCEs, and all-cause mortality, into a composite outcome, patients continuing sLPDs would exhibit significantly lower risks of the composite outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, regarding safety issues, previous studies have proven that, if the daily calorie intake is sufficient, sVLPDs or sLPDs in CKD patients could be safe, and even had some metabolic benefits, namely less hyperphosphatemia, less hyperparathyroidism, lower blood pressure, and gut microbiota modulation, which may additionally contribute to long-term cardiovascular protective effect and patient survival. One previous cohort study demonstrated that serum urea level is associated with CV outcomes in CKD patients, and further suggested a reduction of urea by nutritional therapy may thus be beneficial in reducing CV risks [ 33 ]. Actually, in this study, if we combined all common adverse events in CKD patients, including ESKD requiring dialysis, MACCEs, and all-cause mortality, into a composite outcome, patients continuing sLPDs would exhibit significantly lower risks of the composite outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…According to the KDIGO [25] and the Cardiovascular Stroke Endpoint Definitions for Clinical Trials [26], ATH CVDs include stroke or MI (whether fatal or not) and hospitalization for silent ischemia, unstable angina, transient ischemic attacks, intrastent thrombosis, peripheral artery disease (PAD), percutaneous coronary interventions or coronary artery bypass grafts, vascular surgery, amputation, and revascularization for coronary artery disease (CAD) or PAD. Furthermore, PAD can be defined as a history of amputation, angioplasty, or lower limb bypass prompted by ATH distal ischemic lesions [8,27].…”
Section: Atheromatous Cardiovascular Diseasesmentioning
confidence: 99%
“…Non-ATH CVD encompasses other types of CVD, including sudden cardiac death or death from heart failure (without a history of CAD), hospitalization for heart failure (again with no history of CAD), cardiac fibrosis, atrial fibrillation or other arrhythmia disorders, diastolic dysfunction, arterial stiffness, cardiomyocytes hypertrophy, vascular calcification, or valvular heart disease [8,27,32]. Prior cohorts concluded that the prevalence of heart failure increased markedly with CKD progression and affected 65 to 70% of patients with end-stage renal disease (ESRD) [33].…”
Section: Non-atheromatous Cardiovascular Diseasesmentioning
confidence: 99%
“…Urea serves as a crucial biomarker for the detection and clinical evaluation of urological illnesses [ 191 , 192 ]. Human urine typically has urea concentrations between 155 and 390 mM.…”
Section: Overview Of Lc Droplet-based Biosensors For Poc Diagnosis Of...mentioning
confidence: 99%